ESG investment: What do we learn from its interaction with stock, currency and commodity markets?. (6th December 2020) - Andersson, Emil; Hoque, Mahim; Rahman, Md Lutfur; Uddin, Gazi Salah; Jayasekera, Ranadeva
Abstract: This paper examines ESG portfolio's causal relationship with conventional and ethical equity prices, exchange rates and commodity prices. Using multi‐scale wavelet decomposition, asset returns are decomposed into three timescales (short‐, medium‐ and long‐term), and a three‐step filtered framework is used to explore dynamic non‐linear linkages. We document significant bidirectional causal relationship between ESG, conventional and ethical equity portfolio returns. While the causality persists from the short‐ to medium‐term, it is relatively weaker in the long‐term. We further observe statistically significant causality running from ESG portfolio returns to currency and commodity returns. This causality is strongest in the short‐term, turns weaker in the medium‐term and, in some instances, disappears in the long‐term. These results are generally robust for the use of original returns and VAR‐filtered returns. However, as we control for conditional heteroskedasticity in the return series, the causality appears weaker particularly between ESG portfolio and commodity returns. Our results have important implications for planning portfolio allocation and devising hedging and diversification strategies.